지역사회획득폐렴 환자의 중증도 평가에서 Procalcitonin 유용성 - 박훈표; Hun Pyo Park; 이정수; Jung Soo Lee; 장예수; Ye Su Jang; 김민수; Min Su Kim (Tuberculosis and respiratory diseases, 2009)
Background: Thus far, research studies on community-acquired pneumonia (CAP) have focused on its clinical severity. Recently, it has been determined that procalcitonin (PCT) level is correlated with severity of CAP. A retrospective study conducted at our hospital used risk predictability and PCT to determine whether or no PCT is useful in assessing the severity of CAP. Methods: This study covered 92 CAP cases that were admitted to the respiratory department at Changwon Fatima Hospital between July 1, 2008 and June 30, 2009. All enrolled subjects were measured for infection markers and risk predictability. Results: Based on hospital admission data, enrolled subjects had Pneumonia Severity Index (PSI) scores serving as risk predictors showed that both PCT and white blood cell (WBC) were statistically significant as infection markers (p=0.001, 0.037). Thus, this study used ROC curves in PSI for data analysis. As a result, it was determined that the area under curve (AUC) of PCT and WBC was 0.694 and 0.593 respectively, indicating that PCT has a higher test value for WBC, when PCT was higher than 0.745 ng/mL. In addition, it was found that PCT levels higher than 0.745 ng/mL had higher PSI scores than the group with PCT lower than 0.745 ng/mL (p=0.032). Conclusion: In order to predict risk of pneumonia cases admitted due to symptoms of CAP, it is important to consider PCT as well as PSI, and follow-up monitoring of PCT cases.